USE OF PROGESTERONE IMPREGNATED INDIGENOUS SPONGES ALONG WITH PMSG FOR THE INDUCTION OF CYCLICITY IN ANESTROUS MURRAH BUFFALO - SAINI, A; LUTHRA, R A; PANDEY, A K; NANDA, T; KUMAR, L (The Indian Journal of Animal Reproduction, 2022)
Twenty one anestruos Murrah buffalo were equally divided to receive indigenously prepared intravaginal sponges containing 1.20, 1.40 and 1.60 g progesterone for 8 days followed by administration (i.m.) of 400 IU PMSG on the day of sponge removal. All the buffalo exhibited estrus between 36-72 h after sponge removal with average duration of estrum as 20.66±0.52 h (16-24 h). The conception rate in S1.20, S1.40, S1.60 group was 42.9, 28.6 and 42.9%, respectively on induced estrus with an overall pregnancy rate of 71.4, 28.6 and 57.1%, respectively on subsequent estrus. Plasma progesterone increased (p<0.05) subsequent to sponge insertion in all the groups. In brief, considering the estrus induction response, conception rate and cost effectiveness, the indigenous sponges containing 1.20 g progesterone along with PMSG may be recommended for induction of cyclicity in anestrous buffalo